On prognostic connection between hard cosmic ray flux decrease and leaps of cardiovascular diseases in 2008–2009 in Vilnius - STYRA, Dmitrijus; JUOZULYNAS, Algirdas; USOVAITĖ, Ana; GASPARIŪNAS, Jonas (Acta medica Lituanica, 2011)
Data on a prognostic relationship between the hard cosmic ray flux (HCRF) and the leaps of cardiovascular diseases (CVD) in Vilnius in 2008–2009 are presented. A gamma spectrometer with a scintillation detector were used to register the HCRF near the ground surface. Data on CVD over a period of 24 months (2008–2009) were obtained from the Vilnius Ambulance Service. Information on CVD was selected for all age groups in accordance with the international codes for identification of diseases (ICD). The present study was restricted to time periods when the cosmophysical and medical data could be compared. For the processing of experimental results, empirical criteria in the analysis of HCRF and CVD were used. The criterion in HCRF change is a decrease of HCRF values by 200 impulses and more during a period of 4 hours. The CVD number exceeding the monthly average value by 10, 15, 20% was analysed. A correlation between the above parameters was studied in the range of 1–3-day period. The efficiency of the prognosis of CVD leaps by HCRF decrease in 1–2 days in 2008 was 74–82% and in 2009 65–70%, and for 2–3 days in 2008 54–60% and in 2009 63–65%. The human factor was analysed, too. Keywords: hard cosmic ray flux, cardiovascular diseases, connection, human factor
Keywords: hard cosmic ray flux; cardiovascular diseases; connection; human factor